Photocatalytic reactors with suspended and immobilized TiO 2 : Comparative efficiency evaluation - Manassero, Agustina (2017)
The efficiency of three photocatalytic reactor configurations for the degradation of the micropollutant clofibric acid in water was assessed. The following reaction systems were tested: (i) a slurry reactor with suspended TiO2 particles; (ii) a fixed-film reactor with TiO2 immobilized onto the reactor window; and (iii) a fixed-bed reactor filled with TiO2-coated glass rings. The influence of the catalyst concentration in the suspended system and the number of the catalyst coatings in the immobilized systems were evaluated. The performances of the reactors, under the experimental condition of highest reaction rate for each configuration, were compared with the aid of two parameters: (i) the photonic efficiency (g), which is the ratio of the reaction rate to the rate of incident photons; and (ii) the quantum efficiency (gRxn), which is the ratio of the reaction rate to the photon absorption rate. The obtained values of gRxn were 4.59, 2.96 and 2.02% for the slurry reactor, the fixed-bed reactor and the fixed-film reactor, respectively. Although the slurry reactor was the most efficient configuration, the fixed-bed reactor rendered a value of quantum efficiency only one third lower than the suspended system, making this configuration very convenient for photocatalytic reactions. The analysis of the reaction rate, the photon absorption rate and the quantum efficiency are essential to rationally improve the design, configuration and experimental conditions of photocatalytic reactors.